The role of digitalization in the FDI – income inequality relationship in developed and developing countries - Nguyen, Van Bon (2023)
Purpose: The study aims to use individuals using the internet and fixed broadband subscriptions as a proxy for digitalization to empirically assess the effects of Foreign Direct Investment (FDI), digitalization, their interaction on income inequality in developed and developing countries from 2002 to 2019. Design/methodology/approach: The paper used the system general method of moments (GMM) estimators for 30 developed and 35 developing countries. Findings: FDI increases income inequality in developed countries but decreases it in developing countries, digitalization reduces income inequality in both groups, interaction term narrows income inequality in developed countries but widens it in developing countries. Originality/value: The paper is the first to introduce digitalization into the FDI – income inequality relationship. Furthermore, it provides empirical evidence to show the difference in the role of digitalization in this relationship between developed and developing countries.